Alternatives to Biologics in Management of Knee Osteoarthritis: A Systematic Review. Issue 2 (June 2018) - Hassan, Fadi; Murrell, William D.; Refalo, Andrew; Maffulli, Nicola
Abstract : Background: Knee osteoarthritis (KOA) is a common condition encountered by physicians. KOA is addressed by a wide array of modalities including a number of nonbiological treatments. Methods: PubMed, ISI Web of Science, and SPORTDiscus were searched for level 1 to 4 studies published from inception to August 2017. Results: A total of 18 studies were evaluated and results demonstrated moderate supporting evidence for prolotherapy and limited evidence for botulinum toxin type A, sodium bicarbonate and calcium gluconate, and low–molecular weight fraction of 5% human serum albumin. Evidence for local anesthetic agents was conflicting. Conclusion: There is moderate supportive evidence for the effectiveness of prolotherapy in improving pain and function in both, short-term and long-term. Limited supporting evidence found for botulinum toxin type A, sodium bicarbonate and calcium gluconate, and low–molecular weight fraction of 5% human serum albumin in improving pain and function. There is conflicting evidence for the use of local anesthetic agents in patients with KOA.